2021
DOI: 10.15304/rge.30.2.6865
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de los Fondos Estructurales para Innovación sobre la innovación empresarial: un análisis a través de los indicadores de empresas participantes en el Programa FEDER-Innterconecta de Galicia

Abstract: En este trabajo realizamos una evaluación del impacto del programa FEDER-Innterconecta (desarrollado en el marco del Fondo Tecnológico 2007-2013) en los principales indicadores de innovación empresarial en Galicia. De entre las diferentes líneas de actuación diseñadas, centramos el análisis en las dos primeras convocatorias gallegas del programa FEDER-Innterconecta pertenecientes a este “Programa Operativo por y para el beneficio de la I+D+i empresarial”, cuyo período de implementación abarca hasta el año 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Support through the ESIF for the financing of technological innovation has shown mixed results over time. us, it is possible to find literature defending positive results of technological innovation policies for the business fabric (Musyck & Reid, 2007;Segarra-Blasco, 2018;Le & Jaffe, 2017;Bronzini & Piselli, 2016), while other studies show moderately positive results in peripheral contexts (Sande & Vence, 2021), or even non-existent results for some contexts (Blasio, Fantino & Pellegrini, 2015).…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…Support through the ESIF for the financing of technological innovation has shown mixed results over time. us, it is possible to find literature defending positive results of technological innovation policies for the business fabric (Musyck & Reid, 2007;Segarra-Blasco, 2018;Le & Jaffe, 2017;Bronzini & Piselli, 2016), while other studies show moderately positive results in peripheral contexts (Sande & Vence, 2021), or even non-existent results for some contexts (Blasio, Fantino & Pellegrini, 2015).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Despite this, there are some studies conducted in recent years which are focused on the differences produced between firms according to their size, but aimed at not-Andalusian regions (Santamaría & Nieto, 2009;Silva & Carrizo, 2018;Blaschke, Demel & Kotorov, 2021). us, while some studies using the same methodology (Segarra-Blasco, 2018) or different (Benkovskis, Tkacevs & Yashiro, 2019) have found that companies´size is a key factor other authors (Sande & Vence, 2021) found that large enterprises (LEs) have absorbed part of the expected impact in SMEs. Finally, for others (Sande, 2022b) large and medium-sized enterprises have benefited from the impact of ESIF in some indicators, mainly because these companies have been the ones which have lead the projects, and it let them have received more funds and capitalise the project results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Empleando la técnica estadística PSM, estudios recientes (Bachtrögler & Hammer, 2018) han encontrado efectos diferentes de los FFEE y de cohesión en los indicadores de innovación de las empresas manufactureras de seis países europeos 1 . En concreto, en relación a los aumentos de productividad de las empresas, este estudio ha constatado un significativo impacto para las empresas que han empleado recursos del Fondo Europeo de Desarrollo Regional (FEDER), Fondo Social Europeo (FSE) o del Fondo de Cohesión (FC) en España, Italia y Portugal, aunque otras investigaciones no han encontrado esa relación (Fattorini, Ghodsi & Rungi, 2019), o sólo un efecto ligeramente positivo en los indicadores de innovación empresarial (Sande & Vence, 2021) y en las ventas durante la crisis (Maroshegyi & Nagy, 2010;Hartsenko and Sauga, 2012). En el estudio de Bachtrögler & Hammer únicamente las empresas localizadas en Italia y Portugal han incrementado su número de empleados de forma significativa una vez han participado de las políticas de innovación, coincidiendo con resultados de estudios previos Greenbaum, 2006 y 2014;Bernini & Pellegrini, 2014).…”
Section: A El Impacto De Las Políticas Europeas De Innovación Y La Di...unclassified